Financial reporting and corporate innovation: a review of the international literature. (22nd February 2021) - Huang, Hedy Jiaying; Habib, Ahsan; Sun, Sophia Li; Liu, Ying; Guo, Huiting
Abstract: We synthesise the empirical studies on innovation in the accounting, finance, and corporate governance disciplines using Bushman and Smith's corporate transparency framework as our theoretical lens. The review presents competing findings on the association between financial reporting and innovation. Most of the reviewed studies fail to address the critical question of how the financial reporting system affects the interactions among financial development, corporate governance and innovation. We suggest future research, ranging from enriching the theoretical perspectives to incorporating the future of innovation research in the COVID‐19 environment.